Evaluation of utilization of insecticide treated nets among pregnant women in Bayelsa State of Nigeria: a case study of Sagbama community - Odoko, Joseph O.; Nwose, Ezekiel U.; Igumbor, Eunice O. (International Journal of Research in Medical Sciences, 2018)
Background: There has been a roll back mosquito (RBM) program in Nigeria. This study was carried out to determine the effectiveness and utilization of insecticide treated nets (ITNs) among pregnant women in Bayelsa State, Nigeria. Methods: A descriptive survey design was used to assess usage and patient experience. A total of 250 completed survey were returned out of 260 questionnaires distributed. Statistical analysis was in frequency counts and percentages. Results: Over 55% of respondents are aware that the best way to prevent malaria in pregnancy is to always sleep in ITNs. 20% of the respondents lack ITNs due to non-availability in the clinic or unaffordability in the market. Among those that own ITNs, only 31% utilize it every day. Suffocation and skin irritation were reasons for non-utilization. On effectiveness, among those who use their ITNs, 24.3% never suffered malaria or mosquito bite. Conclusions: ITNs utilization seems to have reached the RBM target. However, the study shows patient experience that use of ITNs seems to have limited effectiveness in prevention of malaria during pregnancy, while affordances and quality are barriers to utility. Ministry of Health and especially antenatal and community healthcare workers need to intensify health education campaign to improve attitude and practice of ITNs utility among pregnant mothers. Manufacturers of ITNs also need to improve on the quality of ITNs to reduce skin irritation or suffocation in order to encourage usage among pregnant mothers.